2023
DOI: 10.1002/14651858.cd012648.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Trifocal intraocular lenses versus bifocal intraocular lenses after cataract extraction among participants with presbyopia

Abstract: Trifocal intraocular lenses versus bifocal intraocular lenses a er cataract extraction among participants with presbyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Regarding binocular UIVA and CIVA, a Cochrane database evaluation from 2020 found that trifocal IOLs implantation resulted in better UIVA at one year, without a significant advantage for uncorrected near and distance vision [ 59 ]. A subsequent 2023 evaluation, expanded in patient age range, confirmed these findings [ 10 ]. Additionally, EDOF IOLs, with an achromatic diffractive surface provide a low add foci, extending the range of vision from distance through intermediate, a study with a three-month follow-up, found EDOF IOLs to be a well-tolerated option for correcting far and intermediate vision [ 60 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Regarding binocular UIVA and CIVA, a Cochrane database evaluation from 2020 found that trifocal IOLs implantation resulted in better UIVA at one year, without a significant advantage for uncorrected near and distance vision [ 59 ]. A subsequent 2023 evaluation, expanded in patient age range, confirmed these findings [ 10 ]. Additionally, EDOF IOLs, with an achromatic diffractive surface provide a low add foci, extending the range of vision from distance through intermediate, a study with a three-month follow-up, found EDOF IOLs to be a well-tolerated option for correcting far and intermediate vision [ 60 ].…”
Section: Discussionmentioning
confidence: 74%
“…As a result, the utilization of high-quality IOLs to address pseudo presbyopia has emerged as a significant subject in contemporary cataract surgery practices [ 7 ]. Beyond standard monofocal IOLs, current clinical practice often involves multifocal IOLs (bifocal and trifocal), EDOF IOLs, and enhanced monofocal IOLs [ 8 10 ]. While standard monofocal IOLs focus light at a single predetermined distance, necessitating additional refractive correction for varying distances [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the advancements in refractive cataract surgery and the widespread adoption of presbyopia-correcting IOLs [ 1 ], patients with cataracts now have a broader range of options available. These options promise to provide spectacle independence across various distances, including far, intermediate, and near vision [ 2 , 3 ]. Various presbyopia-correcting IOLs, such as multifocal IOLs and extended depth of focus intraocular lenses(EDOF IOLs), are available to fulfill visual needs at different distances [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of premium intraocular lenses (IOLs) has played a major role in this evolution over the past decade. In addition to the tried and tested monofocal IOL, multifocal, toric and extended depth of focus (EDOF) IOLs have enabled surgeons cater to the individual visual needs of their patients [2][3][4]. Ocular biometry has also improved significantly from ultrasound technology to optical methods using partial coherence interferometry, optical low-coherence reflectometry and more recently, swept-source OCT-based machines that are accurate even in dense cataracts [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%